Pemberdayaan Wirausaha Perempuan melalui Peningkatan Kapasitas Pemasaran Digital di Desa Kepuharjo, Kecamatan Karangploso - Sri Budi Cantika Yuli; Bambang Widadgo; Zainal Arifin (JOURNAL OF ECONOMIC AND SOCIAL EMPOWERMENT, 2026)
This community service program focuses on empowering women entrepreneurs in Desa Kepuharjo, Karangploso District, Malang Regency through social selling training. The program is a continuation of previous entrepreneurship training led by Ibu Zulaikah, where the group successfully started a brownie baking business. However, they face challenges in digital marketing knowledge and effective communication skills to build consumer relationships. The main problems are low understanding of digital marketing strategies, particularly in using social media to increase sales, and limited skills in effective communication with consumers. To address these issues, the program is designed to provide understanding about social selling strategies, including how to utilize digital platforms to promote products. The methods used include socialization, training, technology implementation, and continuous mentoring. The expected outcomes include increased product sales, strengthened brand awareness, and enhanced digital skills among participants. Through this training, women entrepreneurs in Desa Kepuharjo are expected to become more economically independent and improve their family's quality of life.